Bibliometric analysis of the scientific production using computed microtomography presented at the Brazilian Society of Dental Research annual meetings (Research, Society and Development, 2021)
Computed microtomography uses the principle of x-rays to form two- and three-dimensional images of small samples with high resolution. The annual meeting of the Brazilian Society of Dental Research is the largest event of scientific production in Dentistry in the country. The profile of the papers exhibited can identify characteristics of the scientific research produced nationally. The aim of this study was to retrospectively analyze the scientific production involving micro computed tomography (Micro-CT) in the supplements of SBPqO meetings from 2009 to 2018. After reading the annals of all years using the descriptors “Computed Microtomography”, “Micro-CT”, “MicroCT”, “mCT”, “mTC” and “µCT”, the final sample was a total of 348 studies using Micro-CT. The year with the highest number of abstracts was 2016 (22.7%; n=79). The studies were most frequent in the southeastern region (86.2%; n=300), that presented the most studies were Endodontics (35.0%; n=122) and the most sample used human dental elements (53.7%; n=187). There was an increasing increase in the number of research involving Micro-CT, but there was a greater concentration for the Southeast region and in the area of endodontics. Thus, the need for knowledge dissemination is highlighted so that other areas can also use this tool and increase the scope of dental production.